2011
DOI: 10.1002/cphc.201100339
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Potentials and Acidity Constants of Mn Superoxide Dismutase Calculated by QM/MM Free‐Energy Methods

Abstract: We used two theoretical methods to estimate reduction potentials and acidity constants in Mn superoxide dismutase (MnSOD), namely combined quantum mechanical and molecular mechanics (QM/MM) thermodynamic cycle perturbation (QTCP) and the QM/MM-PBSA approach. In the latter, QM/MM energies are combined with continuum solvation energies calculated by solving the Poisson-Boltzmann equation (PB) or by the generalised Born approach (GB) and non-polar solvation energies calculated from the solvent-exposed surface are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 133 publications
(141 reference statements)
3
82
0
Order By: Relevance
“…The QTCP calculations were performed as has been described before: [72][73][74] First, each state of interest was optimised by QM/MM, keeping system 2 fixed at the crystal structure. Then, the protein was further solvated in an octahedral box of TIP3P water molecules, 75 extending at least 9 Å from the QM/MM system.…”
Section: Qtcp Calculationsmentioning
confidence: 99%
“…The QTCP calculations were performed as has been described before: [72][73][74] First, each state of interest was optimised by QM/MM, keeping system 2 fixed at the crystal structure. Then, the protein was further solvated in an octahedral box of TIP3P water molecules, 75 extending at least 9 Å from the QM/MM system.…”
Section: Qtcp Calculationsmentioning
confidence: 99%
“…This reflects that the oxidation state of the Mo ion has changed in SP and also partly in TS2, something that is frequently problematic to describe with the DFT functionals, giving a strong dependence on the amount of exact exchange of the functionals. 66,67 To get an indication of which DFT functional gives the more reliable results, we estimated the electronic energies for the stationary structures with the LCCSD(T0) method (correcting for basis set incompleteness and domain errors with an MP2 correction as described in the Methods section). In the LCCSD(T0) calculations, the number of pairs included in the CCSD iterations (and the groups included in the triples list) are controlled by distance criteria.…”
Section: Effect Of the Dft Functionalmentioning
confidence: 99%
“…Test calculations at the semiempirical level have shown that this is does not affect the final free energies significantly. 70 The QTCP calculations were performed as previously described, 68,69,71,72 with simple extensions to the QM/MM-2QM case: First, each redox state was optimised by QM/MM-2QM, using a solvated spherical system with a radius of 38 Å. 37 Second, the total system was moved into a periodic octahedral box and was further solvated with water molecules extending at least 9 Å from the original system, giving a total of 12270 water molecules (a set of QTCP calculations in which the solvent shell was increased to 15 Å or 19803 water molecules was also performed).…”
Section: Qtcp-2qm Calculationsmentioning
confidence: 99%
“…77 Finally, T is the temperature and S QM/MM is the entropy, calculated from the frequencies, using a normal-mode harmonicoscillator and ideal-gas approximation. 75 In this investigation, we assume that the contribution from the surrounding protein cancels between the reactant and the product, as has been done before, 72,75 so only the entropy of the isolated QM systems in vacuum was considered. Several variants of QM/MM-PBSA are available.…”
Section: Mementioning
confidence: 99%